Isolation and study of biological properties of Bordetella bronchiseptica-specific bacteriophages - T. A. Kochetova; V. V. Yuskevich; G. T. Sadykova; V. M. Popova (Ветеринария сегодня)
The paper presents results of our studies on isolation of bacteriophages active against Bordetella bronchiseptica. Three new bacteriophages were recovered from clinical material of animals with respiratory disease signs: vB_BbrS_2/200220.7.2, vB_BbrS_4/200220.7.1, vB_BbrM_5/200220.7.2. The lytic activity of isolated bacteriophages determined by the method of agar layers varied from (2.3 ± 1.4) × 108  to (9.0 ± 0.2) × 108  BOE/ml, and the lytic spectrum ranged from 61.5 to 76.9%. The bacteriophage titer stability was shown during 8-month storage of phage lysate with no preservative added. The morphology of bacteriophage negative colonies was tested in various nutrient media and analyzed based on two parameters: size and transparency. Dissociation of negative colonies into clear colonies, cloudy colonies, and clear colonies with cloudy halos was observed in the media. Plaques also varied in size from 0.6 ± 0.2 to 2.6 ± 0.1 mm. High levels of temperature stability were noted during exposure of bacteriophages to high temperatures ranging from +40 to +95 °C in 5 °C step. The study of specificity showed that the isolated bacteriophages lyse closely-related bacteria. In the course of electron microscopic testing of each bacteriophage such parameters as the average diameter of the head and the average length of the tail were determined. In accordance with the international classification of viruses by morphological characteristics the vB_BbrS_2/200220.7.2 and vB_BbrS_4/200220.7.1 phages have been assigned to the family Siphoviridae, vB_BbrM_5/200220.7.2 bacteriophage has been assigned to the family Myoviridae. The obtained results of in vitro studies have shown that the isolated bacteriophages can be prespective in veterinary use for phage therapy of Bordetella bronchiseptica-induced diseases.